A study on the presumption under Section 113 of the Malaysian Evidence Act 1950; with special reference to legal position in other commonwealth countries / Nabihah Ishak … [et al.] - Ishak, Nabihah; Hamzah, Nurellma; Sallehudin, Nur Fatin Nabila; Dyana Anizan, Nor Amalina (2014)
Section 113 of the Malaysian Evidence Act 1950 gives protection to rapist who is below the age of 13 years old from being charged. The provision provides for irrebuttable presumption of law even there is concrete evidence against the offender. Other commonwealth countries like United Kingdom, Hong Kong, Singapore and Australia had completely abolished the said presumption from their legal system. By seeing the development of the law in other Commonwealth countries, Malaysia is still left behind in the aspect of advancement and development of the law particularly Section 113 of the Malaysian Evidence Act 1950. In order to overcome that, some changes need to be considered. Section 113 of the Malaysian Evidence Act 1950 can either be abolished completely, following the mentioned commonwealth countries' position, or the presumption can be amended to be rebuttable. Other than that, the age provided in the section can also be reduced to 10 years old in line with that provided in Section 82 of the Malaysian Penal Code.